Sedimentary Records of Contaminant Inputs in Frobisher Bay, Nunavut (2017-2018) ... : Registres sédimentaires des apports de contaminants dans la baie de Frobisher, Nunavut (2017-2018) ... - Bartley, Meaghan C.; Tremblay, Tommy; De Silva, Amila; Kamula, Michelle; Ciastek, Stephen; Kuzyk, Zou Zou (Observatoire global du Saint-Laurent, 2023)
This dataset includes geochemical and contaminant data measured in surface sediments and sections of sediment cores collected from Koojesse Inlet and other locations in Frobisher Bay, Nunavut. Sediment cores and surface sediment were collected throughout Koojesse Inlet in 2017 by the Canada-Nunavut Geoscience Office aboard MV Nuliajuk vessel. Sediment cores were collected from inner and outer Frobisher Bay in 2018 by University of Manitoba researchers onboard the CCGS Amundsen icebreaker. Geochemical parameters measured in sediment core samples included radioisotopes (210Pb and 137Cs), carbon and nitrogen content, and stable isotopes (δ13C and δ15N). Contaminants measured in selected sediment sections included total mercury (THg), major and trace elements, polychlorinated biphenyls (PCBs), polycyclic aromatic hydrocarbons (PAHs), and per and polyfluoroalkyl substances (PFASs). This project is part of the Coastal Environmental Baseline Program under the Oceans Protection Plan of Fisheries and Oceans Canada. ... : Ce jeu de données comprend des données géochimiques et des données sur les contaminants mesurées dans les sédiments de surface et dans des sections de carottes de sédiments recueillies dans le bras de mer Koojesse et à d'autres endroits de la baie Frobisher, au Nunavut. Des carottes de sédiments et des sédiments de surface ont été prélevés dans l'inlet Koojesse en 2017 par le Bureau géoscientifique Canada-Nunavut à bord du navire MV Nuliajuk. Des carottes de sédiments ont été collectées à l'intérieur et à l'extérieur de la baie Frobisher en 2018 par des chercheurs de l'Université du Manitoba à bord du brise-glace Amundsen du CCGS. Les paramètres géochimiques mesurés dans les échantillons de carottes de sédiments comprenaient les radio-isotopes (210Pb et 137Cs), la teneur en carbone et en azote et les isotopes stables (δ13C et δ15N). Les contaminants mesurés dans certaines sections de sédiments comprenaient le mercure total (ThG), les principaux éléments et les oligo-éléments, les polychlorobiphényles (PCB), ...